1985
DOI: 10.7901/2169-3358-1985-1-385
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Oil Spill Considerations: Protection and Cleanup

Abstract: Oil spills occurring in freshwater (and upper estuarine) environments produce different effects than similar spills in marine environments, and thus require different considerations in protection and cleanup. Freshwater spills are primarily land- or river-based, and retention time of the oil in the environment takes one of two extremes, either very brief or very long. As in the marine environment, spills in marshes (predominantly grasses and sedges) are generally most destructive, especially when marshes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Os mapeamentos realizados pela NOAA (2004,2006) ressaltam que os critérios como tipo de substrato e declividade da margem são imprescindíveis para prever como o óleo irá impactar o ambiente, já que afetam a permeabilidade e o tempo de permanência do poluente. A diferenciação das características de derramamentos de óleo apresentado em Baca et al (1985) para ambientes de água doce de alta ou baixa energia ajudou na definição dos ambientes com maior sensibilidade.…”
Section: Definição De Critérios Para Classificação Da Sensibilidade Dos Ambientesunclassified
See 1 more Smart Citation
“…Os mapeamentos realizados pela NOAA (2004,2006) ressaltam que os critérios como tipo de substrato e declividade da margem são imprescindíveis para prever como o óleo irá impactar o ambiente, já que afetam a permeabilidade e o tempo de permanência do poluente. A diferenciação das características de derramamentos de óleo apresentado em Baca et al (1985) para ambientes de água doce de alta ou baixa energia ajudou na definição dos ambientes com maior sensibilidade.…”
Section: Definição De Critérios Para Classificação Da Sensibilidade Dos Ambientesunclassified
“…Os primeiros trabalhos que abordam a problemática da metodologia para a sensibilidade fluvial são os de Adams et al (1983) e Baca et al (1985), os quais classificaram a sensibilidade ambiental a partir de variáveis como: tempo de recuperação dos habitats; persistência do óleo; importância das espécies; singularidade dos habitats e grau de danos ao habitat decorrentes da limpeza.…”
Section: Introductionunclassified
“…In the aftermath of the spill, it became difficult to determine whether the impacts observed in benthic and riparian environments were the result of oiling or remediation efforts (Fitzpatrick et al 2015; Lee et al 2015). Freshwater remediation also requires different considerations relative to marine systems, which have greater energy and wave action, speeding up oil dispersion and breakdown into more biodegradable components; freshwater systems are relatively more sheltered, low‐energy environments and necessitate different considerations when managing a spill (Baca and Getter 1985). Surfactant‐containing surface washing agents (SWAs) have been suggested as a potential tool in freshwater systems where energy is lower and as a supplement to dredging techniques by facilitating the removal of oil from shorelines and allowing recovery of oil via the open water (Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to weather limitations, recovery of oil using physical means is highly dependent on the thickness of the oil slick 10,13,16,25 . So as the slick becomes thinner and moves, the efficiency of recovery decreases 26 .…”
Section: Physical and Biological Remediationmentioning
confidence: 99%
“…Researchers have observed that the microbial community in samples of oil contaminated water, were able to degrade the oil into carbon dioxide and non-toxic daughter products through natural attenuation 27,30,31 . Other studies have shown that the addition of nutrients to the system can stimulate bacterial growth and encourage the breakdown of the oil in systems where nutrients are limiting 10,11,14,25,29,31,32 . This method is called biostimulation and was used during the Exxon Valdez spill to stimulate the natural microbial communities on the beaches for a more rapid oil biodegradation.…”
Section: Physical and Biological Remediationmentioning
confidence: 99%